A comparison of the reactivating efficacy of a novel bispyridinium oxime K203 with currently available oximes in VX agent-poisoned rats. (August 2013) - Kassa, Jiri; Zdarova Karasova, Jana; Sepsova, Vendula
<x xml:space="preserve">Abstract</x> The ability of a novel bispyridinium oxime K203 to reactivate VX agent-inhibited acetylcholinesterase was compared with the reactivating efficacy of four commonly used oximes (obidoxime, trimedoxime, methoxime, HI-6) using in vivo model. Our results showed that the reactivating efficacy of the oxime HI-6 is higher than the reactivating efficacy of the other oximes studied including the oxime K203 although the differrences between the oxime HI-6 and some other oximes are not significant, especially in the blood. Based on the obtained data, we can conclude that the antidotal treatment involving the oxime HI-6 brings the higher benefit for the antidotal treatment of acute poisonings with VX agent than other oximes.